Time Consumption and Productivity of Motorbike Timber Extraction in Private Forests - Budiaman, Ahmad; Hardjanto; Limbong, Zest Lively (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Timber extraction in private forests in Indonesia is carried out using appropriate technology. Motorbike extraction is one of the means of timber extraction widely used in private forests in Indonesia. This research aimed to analyze the working time and productivity of timber extraction using motorbikes in private forests. The research was conducted in a private forest in Probolinggo, East Java. The terrain conditions at the study site were partly flat and partly rather steep. The study site can only be accessed through a footpath that is 2 m wide. Observations were made on three motorbikes. The number of trips for each motorbike was 11 trips. The skidding distance was 300 m. Data on timber extraction work time were obtained through video analysis. Production data on timber extraction were obtained through direct measurements in the field. The research showed that the work time spent to transport timber from private forests using motorbikes was 18.18 minutes per trip. The loaded travel spent the highest working time, followed by the empty travel, logs stacking, unloading, and traveling to logs. The efficiency of timber extraction using motorbikes in private forests was 82.11%. The productivity of timber extraction was 0.61 m3/hour or 0.002 m3/hour.m. Keywords: appropriate technology, motorbike, private forests, timber extraction, working time